APPROACH OF THE CARTOGRAPHICAL METHOD FOR THE RESEARCH OF THE ORIGINS OF PLACE NAMES AND SURNAMES OF SOUTHEASTERN LATGALE - Kovaļevska, Otīlija (Via Latgalica, 2016)
The prevailing majority of contemporary village names of Latgale in historical sources can be traced back to the 18th century at least, whereas surnames, many of which have been preserved up to now, were extensively mentioned already in the 18th century and even in earlier documents. The striking similarity between the village names and surnames evidently points to their relatedness and raises questions about their origin. Despite the large number of these onyms, many village names and surnames are unique, characterizing a certain region, parish, or even village. To some extent, surnames in Latgale are a geographical reality, and as well as place names, they can be investigated by means of the cartographic methods.The aim of the article is to demonstrate the benefits of using maps in research of the origins of the place names and surnames in Latgale. Applying the maps, the attempt has been made to look at the formation of village names throughout the centuries as well as to find out what the relationship between the family names and place names is. For this purpose the oldest available sources of place names and surnames of Latgale were used, trying to project them on modern maps and searching for correlations. For the research southeastern Latgale has been chosen, since a relatively large number of the 16th–18th century documents, containing personal names and place names are available regarding this region. Since the field of the research is very wide and each name has its own individual history, only general correlations and traditions were searched for. Nevertheless, the examples mentioned in the article illustrate the opportunities that the projection of ancient sources on the modern map provides.The main sources used in this research were various documents of revision and inventories from the 16th–18th centuries, partly digitized by the National Historical Archives metrics and materials of revision dated to 1772, as well as some other 16th–18th century documents, containing place names and surnames, as well as maps of various periods. To identificate place names on modern maps the Database of Geographical Names http://vietvardi.lgia.gov.lv/ and Map Browser http://kartes.lgia.gov.lv/karte/ maintained by the Latvian Geospatial Information Agency (LGIA) have been used.